Composite negative electrode material and preparation method thereof, negative electrode plate, battery and electronic device

By combining the small layer MXene nanosheets with NiMoO4 nanorods in situ to form a composite negative electrode material, the problem of insufficient performance of traditional negative electrode materials in sodium ion batteries is solved, and battery performance with high energy density and long cycle life is achieved.

CN119812281AActive Publication Date: 2025-04-11JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510040994.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In sodium ion batteries, traditional graphite negative electrode materials are not suitable for the insertion/deintercalation of sodium ions, resulting in insufficient energy density and cycle life, limiting the commercial application of sodium ion batteries.

Method used

Using composite negative electrode material, a nanosheet structure supported by the nanorod framework is formed by combining a small layer of MXene nanosheet with NiMoO4 nanorods in situ. The high capacity of NiMoO4 and the high conductivity of MXene can be used to improve the dynamic performance and stability of the battery.

Benefits of technology

It achieves high energy density and long cycle life, significantly improves the dynamic performance and stability of the battery, and solves the problem of insufficient performance of traditional negative electrode materials in sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812281A_ABST
    Figure CN119812281A_ABST
Patent Text Reader

Abstract

The invention relates to a composite negative electrode material and a preparation method thereof, a negative electrode plate, a battery and an electronic device. The composite negative electrode material comprises an MXene nanosheet and a NiMoO4 nanorod grown on the MXene nanosheet in situ; the NiMoO4 nanorod forms a nanorod framework on the MXene nanosheet, so as to support the MXene nanosheet; the MXene nanosheet is a few-layer MXene nanosheet, and the number of layers of the MXene nanosheet is less than or equal to 3. The composite negative electrode material has high capacity of the NiMoO4 material and high conductivity of the MXene material, and has excellent battery dynamic performance and electrochemical performance; in addition, the composite negative electrode material prepared by the preparation method provided by the invention is stronger in binding force, and the stability of the obtained battery is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a composite negative electrode material and a preparation method thereof, a negative electrode sheet, a battery and an electronic device. Background Art

[0002] In recent years, as lithium-ion batteries (LIBs) have become more mature, their scope of use and demand have gradually increased. However, lithium-ion batteries still have limited lithium resource reserves, uneven distribution of lithium resources, and high costs. Therefore, under large-scale market demand, it is imperative to find a storage system with lower cost, rich content, and high safety. Since sodium and lithium have similar physical and chemical properties, and the working principles of sodium-ion batteries (SIBs) and LIBs are very similar, they are not only low-cost, but also can draw on the existing process experience of mature lithium-ion batteries. Therefore, they are expected to become a new generation of secondary batteries and an effective substitute for lithium-ion batteries. Among sodium-ion battery materials, the development of negative electrode materials has always been one of the main factors affecting commercialization. Traditional graphite negative electrodes are not suitable for the insertion / deintercalation of sodium ions. Therefore, research and exploration of negative electrode materials with high energy density and long cycle life are urgent issues to be solved in sodium-ion batteries.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a composite negative electrode material and a preparation method thereof, a negative electrode plate, a battery and an electronic device to solve at least one problem existing in the background technology.

[0005] A first aspect of the present invention provides a composite negative electrode material, comprising a MXene nanosheet and a NiMoO4 nanorod grown in situ on the MXene nanosheet; the NiMoO4 nanorod forms a nanorod skeleton on the MXene nanosheet to support the MXene nanosheet; the MXene nanosheet is a few-layer MXene nanosheet, and the number of layers of the MXene nanosheet is ≤3 layers.

[0006] Preferably, the MXene has the general formula M n+1 X n T x ; wherein M is selected from one or more transition metals selected from Sc, Ti, V, Cr or Mo; X is selected from C or N; T x is a surface functional group, wherein the functional group is selected from one or more of hydroxyl, F, Cl and O; n is selected from 1, 2 or 3;

[0007] Further preferably, the MXene is Ti3C2T x .

[0008] Preferably, the length of the NiMoO4 nanorod is 5 μm to 10 μm, and the aspect ratio of the NiMoO4 nanorod is 12.5 to 100;

[0009] Preferably, the mass ratio of the NiMoO4 nanorods to the MXene nanosheets is (1-3): (0.86-4.2).

[0010] The second aspect of the present invention provides a method for preparing the composite negative electrode material provided in the first aspect of the present invention, the preparation method comprising:

[0011] S1: Provide few-layer MXene;

[0012] S2: dissolving the Ni source, molybdate and the few-layer MXene obtained in step S1 in water, performing a hydrothermal reaction to obtain a precursor product, and annealing the product under an inert gas atmosphere to obtain the composite negative electrode material.

[0013] Preferably, step S1 is: mixing LiF and hydrochloric acid, heating, adding Ti3AlC2, etching, ultrasonication, and obtaining a few layers of Ti3C2T x .

[0014] Preferably, step S1 satisfies at least one of the following features (1) to (5):

[0015] (1) The ratio of the mass (g) of LiF to the volume (ml) of hydrochloric acid is 1:(2-200), and the concentration of the hydrochloric acid is 7 mol / L-11 mol / L;

[0016] (2) The mass ratio of LiF to Ti3AlC2 is 1:(0.5-2);

[0017] (3) The heating method is water bath heating, the heating temperature is 25°C to 35°C, and the heating time is 12h to 24h;

[0018] (4) The etching method is magnetic stirring etching, the etching time is 24h to 48h, and a washing step is also included after the etching;

[0019] (5) The ultrasound is performed in an ice bath; the ultrasound is performed in an inert gas atmosphere, and the inert gas is selected from at least one of argon, nitrogen, helium, and neon; the ultrasound time is 1 h to 2 h; and the ultrasound is followed by a centrifugation and drying step.

[0020] Preferably, step S2 satisfies at least one of the following features (1) to (7):

[0021] (1) The Ni source is selected from at least one of nickel nitrate, nickel chloride, and nickel acetate;

[0022] (2) The molybdate is selected from at least one of sodium molybdate, ammonium molybdate and potassium molybdate;

[0023] (3) The molar ratio of the Ni source to the molybdate is 1:(0.5-2);

[0024] (4) The concentration of the few-layer MXene in the water is 1 mg / ml to 4 mg / ml;

[0025] (5) In the precursor product, the molar ratio of Ni element to the few-layer MXene is (1-3): (2-5);

[0026] (6) The temperature of the hydrothermal reaction is 100° C. to 160° C., and the time of the hydrothermal reaction is 5 h to 8 h; after the hydrothermal reaction is completed, the steps of centrifugal washing and drying are also included;

[0027] (7) The heating rate of the annealing is 3°C / min to 5°C / min, the annealing temperature is 450°C to 600°C, and the annealing time is 2h to 5h; the inert gas is selected from at least one of helium, neon, argon and nitrogen.

[0028] The third aspect of the present invention provides a negative electrode plate, which includes a negative electrode active material, and the negative electrode active material is the composite negative electrode material provided by the first aspect of the present invention or the composite negative electrode material prepared according to the preparation method provided by the second aspect of the present invention.

[0029] A fourth aspect of the present invention provides a battery, comprising the negative electrode plate provided by the third aspect of the present invention.

[0030] A fifth aspect of the present invention provides an electronic device, comprising the battery provided by the fourth aspect of the present invention.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention provides a composite negative electrode material and a preparation method thereof, a negative electrode plate, a battery and an electronic device. The composite negative electrode material is formed by in-situ combining a few-layer MXene nanosheet with a NiMoO4 bimetallic nanorod to form a nanosheet structure supported by a nanorod skeleton, so that the material has both the high capacity of the NiMoO4 material and the high conductivity of the MXene material. The composite negative electrode material utilizes the Ni / Ni 2+ with Mo / Mo 6+The reversible redox reaction between MXene and the electrolyte has a higher theoretical capacity. Due to the high conductivity of MXene itself, the composite negative electrode material structure is rich in ions and charge transfer channels, which greatly reduces the charge transfer resistance between the solid and liquid phases and thus accelerates the charge transfer rate inside the battery. In addition, since the present invention uses a MXene material with a few-layer nanosheet structure, it has excellent conductivity and is not easy to form accumulation between the sheets, thereby significantly improving the kinetic performance of the battery.

[0033] In addition, the preparation of the composite negative electrode material provided by the present invention first adopts a hydrothermal method to allow NiMoO4 and MXene to combine through van der Waals force to form a precursor product, and then forms a NiMoO4 / MXene composite material through medium-temperature sintering, thereby realizing the in-situ combination of NiMoO4 nanorods and MXene with a few-layer nanosheet structure, so that the NiMoO4 nanorods grow in situ on the few-layer MXene to form a nanorod skeleton to support the few-layer MXene nanosheets, so that the binding force between the prepared composite materials is stronger than that of the precursor product, and the stability of the battery using it as the negative electrode active material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0035] Figure 1 The Ti3C2T prepared in Example 2 of the present invention x SEM image of the sample.

[0036] Figure 2 This is the SEM image of NiMoO4 nanorods prepared in Comparative Example 2 of the present invention.

[0037] Figure 3 The Ti3C2T prepared in Example 2 of this application x / NiMoO4 composite material SEM image. DETAILED DESCRIPTION

[0038] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is a detailed description by listing specific embodiments. Wherein, the drawings are not necessarily drawn to scale, and local features can be enlarged or reduced to more clearly show the details of local features. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional experimental conditions. Reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0039] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0040] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0041] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0042] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0043] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0044] As an emerging two-dimensional material, MXenes materials can form nanosheet materials containing hydroxyl, oxygen and fluorine functional groups after hydrofluoric acid etching. The various chemical compositions and rich functional groups make MXenes materials have good interfaces and high conductivity, and thus show great potential in the field of energy storage. However, compared with traditional carbon materials, the electrochemical performance of MXenes needs to be continuously improved. At present, although sulfur-doped MXenes technology is widely used to improve its electrochemical performance, the use of H2S as a sulfur source is highly toxic, environmentally unfriendly, and difficult to recycle. Patent CN109786743B improves the sodium storage performance of MXenes by sulfur doping, but the improvement in kinetics and capacity is not obvious. In addition, during the sodium ion insertion / extraction process, due to the action of van der Waals forces and hydrogen bonds, MXene materials with multi-layer nanosheet structures are prone to stacking between nanosheets, thereby hindering the diffusion of sodium ions.

[0045] On the other hand, ternary metal molybdates as electrode materials have also attracted the attention of scientific researchers due to their high theoretical capacity and adjustable morphology. However, molybdates themselves have poor electrical conductivity and large volume expansion during the cycle, which can easily lead to structural collapse and deterioration of cycle life. Patent CN110350184B synthesizes NiMoO4 using Ni-MOF as a substrate. Although it solves the problem of poor conductivity, it does not have a good effect on structural protection. Patent CN109911947B ensures structural changes by producing core-shell structured NiCo2O4@NiMoO4 materials, but the core-shell structure increases the ion transmission distance, and the thickness of the core-shell layer cannot be accurately regulated.

[0046] In view of this, the present invention provides the following technical solutions:

[0047] [Composite negative electrode materials]

[0048] A first aspect of the present invention provides a composite negative electrode material, comprising a MXene nanosheet and a NiMoO4 nanorod grown in situ on the MXene nanosheet; the NiMoO4 nanorod forms a nanorod skeleton on the MXene nanosheet to support the MXene nanosheet; the MXene nanosheet is a few-layer MXene nanosheet, and the number of layers of the MXene nanosheet is ≤3 layers.

[0049] The composite negative electrode material provided by the present invention combines a few-layer MXene nanosheet with a NiMoO4 bimetallic nanorod in situ to form a nanosheet structure supported by a nanorod skeleton, so that the material has both the high capacity of the NiMoO4 material and the high conductivity of the MXene material. 2+ with Mo / Mo6+ The reversible redox reaction between MXene and the electrolyte has a higher theoretical capacity. Due to the high conductivity of MXene itself, the composite negative electrode material structure is rich in ions and charge transfer channels, which greatly reduces the charge transfer resistance between the solid and liquid phases and thus accelerates the charge transfer rate inside the battery. In addition, since the present invention uses a MXene material with a few-layer nanosheet structure, it has excellent conductivity and is not easy to form accumulation between the sheets, thereby significantly improving the kinetic performance of the battery.

[0050] In the present invention, by selecting MXene nanosheets with a layer number of ≤3 layers, the serious self-stacking phenomenon caused by the large number of MXene nanosheets can be avoided, and the problem that when compounding with NiMoO4 nanorods, the nanorods are only compounded on the surface layer of the MXene material and are difficult to enter the middle stacking part, which is insufficient to support the structure and affect the cycle performance of the battery is effectively solved.

[0051] In certain embodiments, the MXene has the general formula M n+1 X n T x ; wherein M is selected from one or more transition metals selected from Sc, Ti, V, Cr or Mo; X is selected from C or N; T x is a surface functional group, wherein the functional group is selected from one or more of hydroxyl, F, Cl and O; and n is selected from 1, 2 or 3.

[0052] In certain embodiments, the MXene is Ti3C2T x .

[0053] In some embodiments, the length of the NiMoO4 nanorods is 5 μm to 10 μm, for example 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In the present invention, when the length of the NiMoO4 nanorods is within the above range, it can avoid the problem of effectively forming a nanorod skeleton due to a too short length, thereby weakening its supporting effect on the MXene material and affecting the capacity retention rate of the battery; it can also avoid the problem of unevenness and easy breakage during material composite due to the excessive length of the nanorods.

[0055] In some embodiments, the aspect ratio of the NiMoO4 nanorods is 12.5 to 100, for example, 12.5, 15, 17.5, 20, 22.5, 25, 27.5, 30, 32.5, 35, 37.5, 40, 42.5, 45, 47.5, 50, 52.5, 55, 57.5, 60, 62.5, 65, 67.5, 70, 72.5, 75, 77.5, 80, 82.5, 85, 87.5, 90, 92.5, 95, 97.5 or 100, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] In the present invention, when the aspect ratio of the NiMoO4 nanorods is within the above range, it can avoid the problem that a large number of nanorods are exposed during material compounding due to an excessively small aspect ratio, resulting in a weakening of the effect of MXene nanosheets in inhibiting the expansion of NiMoO4 nanorods, thereby causing structural collapse and deterioration of the cycle life; it can also avoid the problem of unevenness and easy breakage during material compounding due to an excessively large aspect ratio.

[0057] In some embodiments, the mass ratio of the NiMoO4 nanorods to the MXene nanosheets is (1-3):(0.86-4.2), for example 1:0.86, 1:1, 1:2, 1:3, 1:4, 1:4.2, 2:0.86, 2:1, 2:3, 2:4.2, 3:0.86, 3:1, 3:2, 3:4 or 3:4.2, but is not limited to the ratios listed, and other ratios not listed within the ratio range are also applicable.

[0058] In the present invention, when the mass ratio of the NiMoO4 nanorods to the MXene nanosheets is within the above range, it is possible to avoid the problem that the MXene nanosheets account for too large a proportion, resulting in the nanorods being unable to form an effective support therefor, causing a stacking problem and thus hindering the diffusion of sodium ions; it is also possible to avoid the problem that the conductivity of the material becomes poor due to the excessive proportion of NiMoO4 nanorods, and during the cycle process, the volume expansion of the nanorods cannot be effectively suppressed due to the small specific gravity of the MXene material, thereby causing structural collapse and thus deteriorating the cycle life.

[0059] [Method for preparing composite negative electrode material]

[0060] The second aspect of the present invention provides a method for preparing the composite negative electrode material provided in the first aspect of the present invention, the preparation method comprising:

[0061] S1: Provide few-layer MXene;

[0062] S2: dissolving the Ni source, molybdate and the few-layer MXene obtained in step S1 in water, performing a hydrothermal reaction to obtain a precursor product, and annealing the product under an inert gas atmosphere to obtain the composite negative electrode material.

[0063] In the present invention, a hydrothermal method is first used to combine NiMoO4 and MXene through van der Waals force to form a precursor product, and then a NiMoO4 / MXene composite material is formed by medium-temperature sintering, thereby realizing the in-situ combination of NiMoO4 nanorods and MXene with a few-layer nanosheet structure, so that the NiMoO4 nanorods grow in-situ on the few-layer MXene to form a nanorod skeleton to support the few-layer MXene nanosheets, so that the bonding force between the prepared composite materials is stronger than that of the precursor product, and the stability of the battery using the composite material as the negative electrode active material is significantly improved.

[0064] In some embodiments, step S1 is: mixing LiF and hydrochloric acid, heating, adding Ti3AlC2, etching, ultrasonication, and obtaining a few layers of Ti3C2T x .

[0065] In certain embodiments, in step S1, the ratio of the mass (g) of LiF to the volume (ml) of hydrochloric acid is 1:(2-200), for example 1:2, 1:20, 1:40, 1:60, 1:80, 1:100, 1:120, 1:140, 1:160, 1:180 or 1:200, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable.

[0066] In certain embodiments, in step S1, the concentration of the hydrochloric acid is 7 mol / L to 11 mol / L, for example, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L or 11 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0067] In certain embodiments, in step S1, the mass ratio of LiF to Ti3AlC2 is 1:(0.5-2), such as 1:0.5, 1:1, 1:1.5 or 1:2, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable.

[0068] In certain embodiments, in step S1, the heating method is water bath heating, and the heating temperature is 25°C to 35°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the heating time is 12h to 24h, for example, 12h, 14h, 16h, 18h, 20h, 22h or 24h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0069] In some embodiments, in step S1, the etching method is magnetic stirring etching, and the etching time is 24h to 48h, for example, 24h, 28h, 32h, 36h, 40h, 44h or 48h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In some embodiments, in step S1, a washing step is further included after the etching, and the washing is centrifugal washing until the pH value is about 6.

[0071] In certain embodiments, in step S1, the ultrasound is ice bath ultrasound; the ultrasound is performed under an inert gas atmosphere, and the inert gas is selected from at least one of argon, nitrogen, helium, and neon; the ultrasound time is 1 h to 2 h, for example, 1 h, 1.5 h or 2 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0072] In certain embodiments, in step S1, the ultrasonication further includes the steps of centrifugation and drying, and the centrifugation time is 0.5h to 1h; the drying is freeze-drying, and the drying time is 24h to 36h, for example, 24h, 28h, 32h or 36h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0073] In certain embodiments, in step S2, the Ni source is selected from at least one of nickel nitrate, nickel chloride, and nickel acetate.

[0074] In certain embodiments, in step S2, the molybdate is selected from at least one of sodium molybdate, ammonium molybdate, and potassium molybdate.

[0075] In certain embodiments, in step S2, the molar ratio of the Ni source to the molybdate is 1:(0.5-2), such as 1:0.5, 1:1, 1:1.5 or 1:2, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable.

[0076] In certain embodiments, in step S2, the concentration of the few-layer MXene in the water is 1 mg / ml to 4 mg / ml, for example 1 mg / ml, 2 mg / ml, 3 mg / ml or 4 mg / ml, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In certain embodiments, in step S2, in the precursor product, the molar ratio of the Ni element to the few-layer MXene is (1-3):(2-5), for example, 1:2, 1:3, 1:4, 1:5, 2:2, 2:3, 2:5, 3:2, 3:4 or 3:5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] In certain embodiments, in step S2, the temperature of the hydrothermal reaction is 100°C to 160°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the time of the hydrothermal reaction is 5h to 8h, for example, 5h, 6h, 7h or 8h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0079] In certain embodiments, in step S2, after the hydrothermal reaction is completed, the steps of centrifugal washing and drying are further included, and the washing is 3 to 6 times of water washing and 2 to 5 times of ethanol washing, for example, 3 times of water washing and 2 times of ethanol washing; the drying temperature is 50°C to 80°C, for example, 50°C, 60°C, 70°C or 80°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the drying time is 10 to 12, for example, 10h, 11h or 12h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0080] In some embodiments, in step S2, the heating rate of the annealing is 3°C / min to 5°C / min, for example, 3°C / min, 4°C / min or 5°C / min, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the annealing temperature is 450°C to 600°C, for example, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the annealing time is 2h to 5h, for example, 2h, 3h, 4h or 5h, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the inert gas is selected from at least one of helium, neon, argon and nitrogen.

[0081] In the present invention, the size of the NiMoO4 nanorods can be controlled by changing the amount of molybdate added in step S2 and process parameters (such as hydrothermal reaction temperature and time); the size, length, aspect ratio of the NiMoO4 nanorods, and the number of layers of the MXene nanosheets and other parameters can be directly or indirectly obtained by scanning electron microscopy (SEM).

[0082] [Negative electrode]

[0083] The third aspect of the present invention provides a negative electrode plate, which includes a negative electrode active material, and the negative electrode active material is the composite negative electrode material provided by the first aspect of the present invention or the composite negative electrode material prepared according to the preparation method provided by the second aspect of the present invention.

[0084] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode current collector can be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The negative electrode active material layer includes a negative electrode active material. In the present invention, the negative electrode active material is the negative electrode material provided in the second aspect of the present invention.

[0085] The negative electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of negative electrode conductive agents include conductive carbon black, conductive graphite, vapor deposited carbon fiber (VGCF), carbon nanotubes, graphene, etc. The binder of the negative electrode improves the bonding performance between the negative electrode active material particles and between the negative electrode active material particles and the current collector. Examples of negative electrode binders include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), cyclodextrin, gelatin, polyvinyl alcohol, polyacrylate, acrylonitrile multipolymer, etc. The mass ratio of each component in the negative electrode active material layer can be conventional.

[0086] The present application has no particular restrictions on the preparation method of the negative electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the negative electrode sheet includes but is not limited to the following steps: dispersing the negative electrode active material, the conductive agent, and the binder in a solvent and mixing them to form a uniform negative electrode slurry, coating the negative electrode slurry on the negative electrode collector, and obtaining the negative electrode sheet after drying, cold pressing, cutting, slitting and re-drying. The solvent of the negative electrode slurry can be a conventional solvent in the art, such as deionized water.

[0087] It should be understood that since the negative electrode plate provided in the present application includes a negative electrode active material, the negative electrode active material is the composite negative electrode material provided in the first aspect of the present invention or the composite negative electrode material prepared by the preparation method provided in the second aspect of the present invention, the beneficial effects of the composite negative electrode material and its preparation method described in any of the above embodiments are applicable to the negative electrode plate.

[0088] [Battery]

[0089] A fourth aspect of the present invention provides a battery, comprising the negative electrode plate provided by the third aspect of the present invention.

[0090] In some embodiments, the battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a sodium ion battery, etc., but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack sodium ion battery, a square hard-shell battery, or a cylindrical hard-shell battery, etc.

[0091] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. Typically, a battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive / negative electrode from short-circuiting, while allowing ions to pass through.

[0092] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode current collector may be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material suitable for the present invention may be various known positive electrode active materials that can be used for sodium ion batteries, which can reversibly embed and deintercalate sodium ions. The positive electrode active material may be a sodium ion positive electrode active material commonly used in the art, preferably selected from sodium iron composite oxides (such as NaFeO2), sodium cobalt composite oxides (such as NaCoO2), sodium chromium composite oxides (such as NaCrO2), sodium manganese composite oxides (such as NaMnO2), sodium nickel composite oxides (such as NaNiO2), sodium nickel titanium composite oxides (such as NaNi0 .5 Ti 0.5 O2), sodium nickel manganese composite oxides (such as NaNi 0.5 Mn 0.5 O2), sodium iron manganese composite oxides (such as Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2), sodium nickel cobalt manganese composite oxides (such as NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), one or more of sodium iron phosphate compounds (such as NaFePO4), sodium manganese phosphate compounds (such as NaMnPO4) and sodium cobalt phosphate compounds (such as NaCoPO4).

[0093] The positive electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of the conductive agent of the positive electrode include one or more of conductive carbon black, carbon fiber (CF), acetylene black, Ketjen black, graphene, carbon nanotubes and carbon microspheres. The binder of the positive electrode improves the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples of the binder of the positive electrode include at least one of a fluorine-containing resin, a polypropylene resin, a fiber-type binder, a rubber-type binder and a polyimide-type binder. The mass ratio of each component in the positive electrode active material layer can be conventional.

[0094] The positive electrode active material layer is obtained by coating a positive electrode slurry containing various components of the positive electrode active material layer and a solvent onto a positive electrode current collector, and then rolling and slitting. The solvent of the positive electrode slurry can be N-methylpyrrolidone (NMP).

[0095] The separator can be a polymer porous separator, an inorganic porous separator or a polymer-inorganic composite porous separator. The polymer porous separator includes a single-layer polymer porous separator and a multi-layer polymer porous separator.

[0096] The electrolyte generally comprises a solvent and a sodium salt. The electrolyte suitable for the present invention may be conventional, for example, the solvent may be one or more selected from dimethyl carbonate (DMC), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or 1,4-butyl propyl ester, more preferably one or more of PC, EC and EMC. The sodium salt may be one or more selected from sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate or sodium perchlorate.

[0097] The battery of the present application also includes a packaging shell for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in a sodium ion battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging shell, and it can be a packaging shell known in the art, as long as it can achieve the purpose of the present application.

[0098] The present invention has no special limitation on the method for preparing the battery, and the technical scheme for preparing the negative electrode material into a battery such as a secondary battery, which is well known to those skilled in the art, can be adopted.

[0099] It should be understood that, since the battery provided in the present application includes the negative electrode plate described in the third aspect of the present invention, the beneficial effects of the composite negative electrode material described in any of the above embodiments are applicable to the battery.

[0100] [Electronic devices]

[0101] A fifth aspect of the present invention provides an electronic device, comprising the battery provided by the fourth aspect of the present invention.

[0102] The use of the battery of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, drones, and sodium ion capacitors, etc.

[0103] It should be understood that, since the electronic device provided in the present application includes the battery described in the fourth aspect of the present invention, the beneficial effects of the composite negative electrode material described in any of the above embodiments are applicable to the electronic device.

[0104] The method of the present invention is described below by means of specific examples. It should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in routine experiments.

[0105] Example 1

[0106] Step S101: First, place 1g of lithium fluoride (LiF) and 40ml of 9M hydrochloric acid (HCl) in a plastic beaker / polytetrafluoroethylene bottle and stir magnetically for 30min. Transfer the plastic bottle to a 35°C water bath. After the temperature stabilizes, add 1g of titanium aluminum carbide (Ti3AlC2, MAX phase) in batches and stir magnetically for 36h. After the water bath reaction is completed, centrifuge the product to pH≈6, ultrasonicate it in an ice bath under argon atmosphere for 1h, centrifuge it for 1h, and freeze-dry it for 36h to obtain a few-layer Ti3C2T x (i.e. few-layer MXene).

[0107] Step S102: 2 mmol nickel nitrate (Ni(NO3)2·6H2O) and 2 mmol sodium molybdate (Na2MoO4·2H2O) and the few-layer Ti3C2T obtained in step S101 are mixed. x Dissolve in 60 mL of deionized water (a few layers of Ti3C2T xThe concentration was 4 mg / mL), and after magnetic stirring for 1 h, it was transferred to a 100 mL polytetrafluoroethylene-lined reactor and subjected to hydrothermal reaction at 160 °C for 8 h. After the hydrothermal reaction, the solution was centrifuged and washed with water 3 times and ethanol 2 times, and dried at 60 °C for 12 h to obtain the precursor product (Ti3C2T in the precursor product x The molar ratio of NiMoO4 material is 2:1). In an argon atmosphere, the temperature was 3℃min -1 The Ti3C2T was obtained by annealing at 450℃ for 2h. x / NiMoO4 composite material (i.e. composite negative electrode material).

[0108] Example 2

[0109] The difference between Example 2 and Example 1 is that in step S102, a few layers of Ti3C2T x The concentration of NiMoO4 nanorods was 2 mg / mL; the aspect ratio of NiMoO4 nanorods was in the range of 35-40, and the length was 7 μm; the Ti3C2T x The molar ratio of NiMoO4 material is 1:1.

[0110] Example 3

[0111] The only difference between Example 3 and Example 1 is that in step S102, the amount of nickel nitrate added is 4 mmol; the amount of sodium molybdate added is 4 mmol; the amount of Ti3C2T3O3 in deionized water is 4 mmol; x The concentration of Ti3C2T x The molar ratio of NiMoO4 material is 1:2.

[0112] Example 4

[0113] The only difference between Example 4 and Example 2 is that the length of the NiMoO4 nanorods is 5 μm.

[0114] Example 5

[0115] The only difference between Example 5 and Example 2 is that the aspect ratio of the NiMoO4 nanorods is 12.5.

[0116] Comparative Example 1

[0117] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 only includes step S101 in Example 1, and the obtained few-layer Ti3C2T x as negative electrode material.

[0118] Comparative Example 2

[0119] Step S102*: Dissolve 2mmol nickel nitrate (Ni(NO3)2·6H2O) and 2mmol sodium molybdate (Na2MoO4·2H2O) in 60mL deionized water, stir magnetically for 1h, transfer to a 100mL polytetrafluoroethylene-lined reactor, and perform hydrothermal reaction at 160℃ for 8h. After the hydrothermal reaction, wash the solution by centrifugation 3 times with water and 2 times with ethanol, and dry at 60℃ for 12h to obtain a precursor product. The precursor product was heated at 3℃min under argon atmosphere. -1 The NiMoO4 nanorods (i.e., negative electrode material) were obtained by annealing at 450℃ for 2h at a heating rate of .

[0120] Comparative Example 3

[0121] The difference between Comparative Example 3 and Example 1 is that in step S102, a few layers of Ti3C2T x The concentration is 10 mg / mL.

[0122] Comparative Example 4

[0123] The difference between Comparative Example 4 and Example 1 is that in step S102, a few layers of Ti3C2T x The concentration is 2 mg / mL; and the annealing step is not included, and only the obtained precursor product is used as the negative electrode material.

[0124] Electrochemical performance test

[0125] Preparation of sodium ion batteries:

[0126] (1) Preparation of negative electrode sheet: The negative electrode materials prepared in the above Examples 1 to 5 and Comparative Examples 1 to 4 are used as negative electrode active materials, carbon black is used as a conductive agent, and CMC is used as a binder. The mixture is mixed in a ratio of negative electrode active material: conductive agent: binder = 8:1:1, and is evenly coated on a negative electrode current collector (Cu foil) on a coating machine. The negative electrode sheet is prepared by roller pressing and slicing.

[0127] (2) Preparation of positive electrode sheet: using a metal sodium sheet as the positive electrode sheet;

[0128] (3) Diaphragm: Glass fiber diaphragm is used as the diaphragm;

[0129] (4) Electrolyte: The electrolyte is prepared by dissolving 1.0 mol / L NaPF6 in diethylene glycol dimethyl ether;

[0130] (5) Battery assembly: The negative electrode sheet, the separator, and the positive electrode sheet were assembled in order and soaked in electrolyte respectively to form a CR2032 button battery in an argon glove box.

[0131] The performance of CR2032 button cells using the negative electrode materials prepared in the above Examples 1 to 5 and Comparative Examples 1 to 4 as negative electrode active materials was tested. The test results are shown in Table 1.

[0132] 1. Test of the first discharge capacity, first charge capacity and first coulombic efficiency: Using Wuhan Blue Electric CT200A battery test system, at 25°C, discharge to 0V at a current density of 0.1A / g, and record the discharge capacity at this time as the first discharge capacity; then charge to 3V at a current density of 0.1A / g, and record the charge capacity at this time as the first charge capacity; first coulombic efficiency = first charge capacity / first discharge capacity*100%.

[0133] 2. 100-week capacity retention rate test: Using Wuhan Blue Electric CT200A battery testing system, at 25°C, discharge to 0V at a current density of 0.1A / g, and then charge to 3V at a current density of 0.1A / g. Record the charging capacity at this time as the first-cycle charging capacity, which is one cycle; repeat the process for 100 cycles, and record the charging capacity of the 100th cycle. Capacity retention rate = 100th cycle charging capacity / first cycle charging capacity * 100%.

[0134] Table 1

[0135]

[0136]

[0137] As shown in Table 1, by comparing Example 2 with Example 4, it can be found that the 100-week capacity retention rate of Example 4 is reduced by 10% compared with Example 2. This is because the composite NiMoO4 nanorods in Example 4 are short rods of 5 μm. The short rods will result in the inability to form an internally connected skeleton, which will deteriorate the supporting capacity of MXene and the effect of MXene in inhibiting the volume expansion of the nanorods, thereby affecting the cycle life; by comparing Example 2 with Example 5, the first effect of Example 5 is higher than that of Example 2, but the capacity retention rate is significantly lower than that of Example 2. This is because the aspect ratio of the NiMoO4 nanorods in Example 5 is relatively small, which leads to most of the nanorods being exposed on the surface of the MXene nanosheets when composited, resulting in more active sites of the material, thereby showing a better first effect, but also resulting in the weakening of the effect of MXene nanosheets in inhibiting the expansion of NiMoO4 nanorods, resulting in a lower capacity retention rate; by comparing Comparative Example 1 with Examples 1 to 5, it can be found that only Ti3C2T xThe charge and discharge capacity of the negative electrode material of the material is significantly reduced compared with the negative electrode material in the embodiment; by comparing Comparative Example 2 with Examples 1 to 5, it can be found that after 100 cycles at a current density of 0.1 A / h, the capacity retention rate of the negative electrode material obtained in Comparative Example 2 is only about 20%, which is much lower than 90% of Example 2, and the first coulombic efficiency is also significantly reduced; by comparing Comparative Example 3 with Examples 1 to 5, it can be found that the capacity retention rate of the negative electrode material obtained in Comparative Example 2 is only about 20%, which is much lower than 90% of Example 2, and the first coulombic efficiency is also significantly reduced. x After the material quality is improved, the first charge and discharge capacity of the obtained negative electrode material is significantly reduced. In addition, by comparing Examples 1 to 5, it can be found that the first coulombic efficiency and 100-cycle capacity retention rate of Example 2 are the best, which shows that although higher NiMoO4 will lead to a higher first discharge specific capacity, too high NiMoO4 will lead to structural instability. By controlling the ratio of MXene material to NiMoO4 to the ratio in Example 2, the electrochemical performance of the obtained battery is more excellent. By directly comparing Comparative Example 4 with Example 2, it can be found that high-temperature sintering of the obtained precursor product can form a NiMoO4 / Mxene composite material, thereby realizing the in-situ combination of NiMoO4 nanorods and Mxene with a few-layer nanosheet structure, thereby making the stability of the obtained negative electrode material higher.

[0138] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A composite negative electrode material, characterized in that: The composite negative electrode material includes MXene nanosheets and NiMoO4 nanorods in-situ grown on the MXene nanosheets; the NiMoO4 nanorods form nanorod skeletons on the MXene nanosheets to support the MXene nanosheets; the MXene nanosheets are few-layer MXene nanosheets, and the number of layers of the MXene nanosheets is ≤3 layers.

2. The composite negative electrode material according to claim 1, characterized in that: The MXene has the general formula M n+1 X n T x ; wherein M is selected from one or more transition metals selected from Sc, Ti, V, Cr or Mo; X is selected from C or N; T x is a surface functional group, wherein the functional group is selected from one or more of hydroxyl, F, Cl and O; n is selected from 1, 2 or 3; Preferably, the MXene is Ti3C2T x .

3. The composite negative electrode material according to claim 1 or 2, characterized in that: The length of the NiMoO4 nanorod is 5 μm to 10 μm, and the aspect ratio of the NiMoO4 nanorod is 12.5 to 100; The mass ratio of the NiMoO4 nanorods to the MXene nanosheets is (1-3): (0.86-4.2).

4. A method for preparing the composite negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: S1: Provide few-layer MXene; S2: dissolving the Ni source, molybdate and the few-layer MXene obtained in step S1 in water, performing a hydrothermal reaction to obtain a precursor product, and annealing the product under an inert gas atmosphere to obtain the composite negative electrode material.

5. The preparation method according to claim 4, characterized in that: Step S1 is: mixing LiF and hydrochloric acid, heating, adding Ti3AlC2, etching, ultrasonication, and obtaining a few layers of Ti3C2T x .

6. The preparation method according to claim 5, characterized in that: Step S1 satisfies at least one of the following characteristics (1) to (5): (1) The ratio of the mass (g) of LiF to the volume (ml) of hydrochloric acid is 1:(2-200), and the concentration of the hydrochloric acid is 7 mol / L-11 mol / L; (2) The mass ratio of LiF to Ti3AlC2 is 1:(0.5-2); (3) The heating method is water bath heating, the heating temperature is 25°C to 35°C, and the heating time is 12h to 24h; (4) The etching method is magnetic stirring etching, the etching time is 24h to 48h, and a washing step is also included after the etching; (5) The ultrasound is performed in an ice bath; the ultrasound is performed in an inert gas atmosphere, and the inert gas is selected from at least one of argon, nitrogen, helium, and neon; the ultrasound time is 1 h to 2 h; and the ultrasound is followed by a centrifugation and drying step.

7. The preparation method according to claim 4, characterized in that: Step S2 satisfies at least one of the following characteristics (1) to (7): (1) The Ni source is selected from at least one of nickel nitrate, nickel chloride, and nickel acetate; (2) The molybdate is selected from at least one of sodium molybdate, ammonium molybdate and potassium molybdate; (3) The molar ratio of the Ni source to the molybdate is 1:(0.5-2); (4) The concentration of the few-layer MXene in the water is 1 mg / ml to 4 mg / ml; (5) In the precursor product, the molar ratio of Ni element to the few-layer MXene is (1-3): (2-5); (6) The temperature of the hydrothermal reaction is 100° C. to 160° C., and the time of the hydrothermal reaction is 5 h to 8 h; after the hydrothermal reaction is completed, the steps of centrifugal washing and drying are also included; (7) The heating rate of the annealing is 3°C / min to 5°C / min, the annealing temperature is 450°C to 600°C, and the annealing time is 2h to 5h; the inert gas is selected from at least one of helium, neon, argon and nitrogen.

8. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode active material, and the negative electrode active material is a composite negative electrode material according to any one of claims 1 to 3 or a composite negative electrode material prepared by a preparation method according to any one of claims 4 to 7.

9. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 8.

10. An electronic device, characterized in that: The electronic device comprises the battery as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of nickel molybdate doped carbon quantum dot negative electrode material of lithium ion battery

    CN109713301A

  • CoMoO4 / Ti3C2 nano composite particle, and preparation method and application thereof

    CN112563038A

  • Composite nano material for sodium ion battery and preparation method of composite nano material

    CN114220961A

  • Coralline cobalt molybdate composite material with oxygen vacancies as well as preparation method and application of coralline cobalt molybdate composite material

    CN114883548A

  • Preparation method of self-supporting membrane and application of self-supporting membrane in preparation of lithium / sodium ion battery composite negative electrode

    CN116364864A